Regio‐ and Stereoselective Aliphatic–Aromatic Cross‐Benzoin Reaction: Enzymatic Divergent Catalysis. Issue 39 (12th August 2016) - Beigi, Maryam; Gauchenova, Ekaterina; Walter, Lydia; Waltzer, Simon; Bonina, Fabrizio; Stillger, Thomas; Rother, Dörte; Pohl, Martina; Müller, Michael
Abstract: The catalytic asymmetric synthesis of chiral 2‐hydroxy ketones by using different thiamine diphosphate dependent enzymes, namely benzaldehyde lyase from Pseudomonas fluorescens ( Pf BAL), a variant of benzoylformate decarboxylase from Pseudomonas putida ( Pp BFD‐L461A), branched‐chain 2‐keto acid decarboxylase from Lactococcus lactis ( Ll KdcA) and a variant of pyruvate decarboxylase from Acetobacter pasteurianus ( Ap PDC‐E469G), was studied. Starting with the same set of substrates, substituted benzaldehydes in combination with different aliphatic aldehydes, Pf BAL and Pp BFD‐L461A selectively deliver the ( R )‐ and ( S )‐2‐hydroxy‐propiophenone derivatives, respectively. The ( R )‐ and ( S )‐phenylacetylcarbinol (1‐hydroxy‐1‐phenylacetone) derivatives are accessible in a similar way using Ll KdcA and Ap PDC‐E469G, respectively. In many cases excellent stereochemical purities (>98 % enantiomeric excess) could be achieved. Hence, the regio‐ and stereochemistry of the product in the asymmetric aliphatic–aromatic cross‐benzoin reaction can be controlled solely by choice of the appropriate enzyme or enzyme variant. Abstract : Divergent biocatalysis : The catalytic asymmetric synthesis of chiral 2‐hydroxy ketones using different thiamine diphosphate dependent enzymes, namely Pf BAL, Pp BFD‐L461A, Ll KdcA and Ap PDC‐E469G, was studied (see scheme). The results show that the regio‐ and stereochemistry of the product in the reaction can be controlled solely by choice of the appropriate enzyme.